FUNCTIONS OF DISCOURSE MARKERS IN ORAL POLITICAL SPEECH - Djumabaeva Jamila Sharipovna; Kenjaeva Gulbadanbegim Alibekovna; Kenjaeva Mumtozbegim Alibekovna (American Journals, 2023)
The article is devoted to the analysis of the linguistic features of modern political discourse (PD). The purpose of the study is to consider the features of the use of discursive markers (DM) in the oral speech of American politicians on the example of television debates. The functions of discursive markers are singled out, and a classification of these speech elements is proposed in relation to the chosen type of political discourse. Examples of the distribution of DM in political speech are analyzed, and an interpretation of the functioning of specific types of DM is given. The characteristics of the intonational design of DM in oral PD are discussed.
Keywords: Political discourse (PD), political debates, discursive markers (DM), classification of DM, functioning and intonation of DM in PD.